IMPACT OF CHANGES IN AGRICULTURAL SPATIAL USE ON SUBAK SUSTAINABILITY - I Ketut Arnawa; I Made Budiasa (International Journal of Applied Science and Sustainable Development (IJASSD), 2022)
Every year there has been a change in the spatial use of agricultural land to non-agriculture, this has an impact on the sustainability of subak in Bali. The main purpose of this study is to analyze the impact of changes in the use of agricultural land on the sustainability of farmers' activities in the Subak area. This research was carried out in the Subak Belumbang area, Tabanan Bali. The study used a qualitative descriptive approach, with a sample of all farmers who experienced a change in the function of subak space utilization for non-agricultural activities and several key informants such as the head of subak and subak administrators. The results of the study found that changes in the use of subak spatial planning for non-agricultural activities had an impact on, the implementation of the subak concept based on the Tri Hita Karana could not work well, and changes in the function of irrigation network channels. To stop the change in the use of agricultural land spatial planning to non-agricultural use, regulations on the utilization of the Regional Spatial Plan and provide strict sanctions for violators. So this research is very important for the sustainability of Subak in the future.